2009
DOI: 10.2527/jas.2009-2094
|View full text |Cite
|
Sign up to set email alerts
|

Short-term foraging dynamics of cattle grazing swards with different canopy structures1

Abstract: The objective of the present experiment was to describe the sward canopy structures of 3 different wheat (Triticum aestivum L.) pastures and relate them to short-term herbage intake rate and foraging dynamics by steers. Pastures were sampled for leaf and stem fractions at the bottom, middle, and top canopy strata. Sward surface heights and tiller and bulk densities were measured. Herbage was separated into stem and leaf, and leaves were then ranked phenologically. Three steers grazed (grazing sessions) 3 diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 35 publications
4
36
0
3
Order By: Relevance
“…This result shows that under strip-grazing management the time spent grazing is a poor indicator of the intensity of ruminal fermentation, which could be associated to sward structural traits and to their effects on the intake rate (Baumont et al, 2004) and the chemical composition of herbage (Noziere et al, 2011). Under rotational stocking, the influence of sward height and of the leaf/stem ratio on bite mass is more highly correlated with green leaf mass than with sward surface height or total herbage mass (Gregorini et al, 2009). Likewise, the intake rate declines progressively as leaves are removed, and the pseudostem corresponds to a greater proportion of the ingested material (Drescher et al, 2006).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…This result shows that under strip-grazing management the time spent grazing is a poor indicator of the intensity of ruminal fermentation, which could be associated to sward structural traits and to their effects on the intake rate (Baumont et al, 2004) and the chemical composition of herbage (Noziere et al, 2011). Under rotational stocking, the influence of sward height and of the leaf/stem ratio on bite mass is more highly correlated with green leaf mass than with sward surface height or total herbage mass (Gregorini et al, 2009). Likewise, the intake rate declines progressively as leaves are removed, and the pseudostem corresponds to a greater proportion of the ingested material (Drescher et al, 2006).…”
Section: Resultsmentioning
confidence: 83%
“…This reduction could be associated to a lower intake rate (Gregorini et al, 2009) and to a lower proportion of green leaf at the end of the paddock in the oldest swards. These data are in agreement with Williams et al (2005), who concluded that the lower rumen fluid pH level observed was a function of the higher intake rate of cows grazing at high herbage allowance.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The animal is considered to move to a new feeding station at the cost of taking steps when intake rate from the current feeding station falls below the threshold level under repeated bites (Searle et al, 2005;Gregorini et al, 2011). Bite number, residence time and intake per feeding station, feeding station number per unit foraging time and step number between feeding stations are major feeding station behavior variables, which reflect profitability or unprofitability of feeding stations (Ruyle and Dwyer, 1985;El Aich et al, 1989;Roguet et al, 1998b;Gregorini et al, 2007Gregorini et al, , 2009Gregorini et al, and 2011Hirata et al, 2008;Shingu et al, 2010). The cost-benefit concept of the feeding station behavior is useful for a better understanding of foraging behavior of animals (Roguet et al, 1998b) and adjusting management strategies of various grazing systems ranging from an intensively managed small paddock of a sown pasture to an extensive rangeland across a landscape (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Ruyle and Dwyer, 1985;El Aich et al, 1989;Gregorini et al, 2011). However, previous studies have focused mainly on relatively short-term (<1 day to about 30 days) variations in feeding station behavior in order to investigate the effects of forage availability (Ruyle and Dwyer, 1985;Roguet et al, 1998b), sward structure (Gregorini et al, 2009), plant species (Hirata et al, 2008), grazing management (Gregorini et al, 2011), animal species (Shingu et al, 2010) and rumen fill (Gregorini et al, 2007). Relatively little information has been reported on how grazing animals modify feeding station behavior seasonally and interannually in response to varying environmental conditions (El Aich et al, 1989;Jiang and Hudson, 1993).…”
Section: Introductionmentioning
confidence: 99%